Answer:
x = - 1, x =
![(1)/(8)](https://img.qammunity.org/2020/formulas/mathematics/college/oishxf3znbtm7sgua7hx3bnp2grk4mwmno.png)
Explanation:
Given
8x² + 7x - 1 = 0 ← in standard form
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 8 × - 1 = - 8 and sum = + 7
The factors are + 8 and - 1
Use these factors to split the x- term
8x² + 8x - x - 1 = 0 ( factor the first/second and third/fourth terms )
8x(x + 1) - 1(x + 1) = 0 ← factor out (x + 1) from each term
(x + 1)(8x - 1) = 0
Equate each factor to zero and solve for x
x + 1 = 0 ⇒ x = - 1
8x - 1 = 0 ⇒ 8x = 1 ⇒ x =
![(1)/(8)](https://img.qammunity.org/2020/formulas/mathematics/college/oishxf3znbtm7sgua7hx3bnp2grk4mwmno.png)